Industrie minière et programmes de développement durable au Sénégal - Bruno Boidin; Serge Francis Simen (Développement Durable et Territoires)
This article compares the perceptions of different local actors about sustainable development programmes put in place by mining companies in Senegal. We built an analytical grid of the characteristics of sustainable development programmes. This grid was used for the qualitative survey. We conclude that, despite the progress made through the initiatives between private and public stakeholders, these programmes are insufficiently integrated and inclusive. The weak inclusiveness leads to a low social acceptability and slows down the evolution of the companies towards a new business model.sustainable development, corporate social responsibility, mining companies, Senegal, inclusion